Product personalisation using personally meaningful data and the creation of new product attributes - Cay Green; Samantha Porter; Guy Bingham (2017)
Some additive manufacture processes can be used to fabricate personalised products. Commercial companies have formed that exploit this fabrication potential, creating co-design environments that allow users to personalise and customise product geometry in new ways. Work carried out at the intersection of art and design takes this a step further, exploring ways in which objects form can be transformed using complex data sets. Interactions that facilitate product personalisation (PP) using data that is meaningful to the owner could stimulate the formation of product attachment, which in turn could extend a products lifespan. However, this new PP potential could lead to the formation of new product attributes that must be mediated by both the designer and the user. This paper explores examples of product/data synthesis and uses them to propose three product attributes that could result from data-driven PP: abstractness, visibility and obtrusiveness.